Decreased serum concentrations of sphingosine-1-phosphate in sepsis. Issue 1 (December 2015) - Winkler, Martin; Nierhaus, Axel; Holzmann, Maximilian; Mudersbach, Eileen; Bauer, Antonia; Robbe, Linda; Zahrte, Corinne; Geffken, Maria; Peine, Sven; Schwedhelm, Edzard; Daum, Guenter; Kluge, Stefan; et al.
Abstract Introduction Sphingosine-1-phosphate (S1P) is a signaling lipid that regulates pathophysiological processes involved in sepsis progression, including endothelial permeability, cytokine release, and vascular tone. The aim of this study was to investigate whether serum-S1P concentrations are associated with disease severity in patients with sepsis. Methods This single-center prospective-observational study includes 100 patients with systemic inflammatory response syndrome (SIRS) plus infection (n = 40), severe sepsis (n = 30), or septic shock (n = 30) and 214 healthy blood donors as controls. Serum-S1P was measured by mass spectrometry. Blood parameters, including C-reactive protein (CRP), procalcitonin (PCT), interleukin-6 (IL-6), lactate, and white blood cells (WBCs), were determined by routine assays. The Sequential Organ Failure Assessment (SOFA) score was generated and used to evaluate disease severity. Results Serum-S1P concentrations were lower in patients than in controls (P < 0.01), and the greatest difference was between the control and the septic shock groups (P < 0.01). Serum-S1P levels were inversely correlated with disease severity as determined by the SOFA score (P < 0.01) as well as with IL-6, PCT, CRP, creatinine, lactate, and fluid balance. A receiver operating characteristic analysis for the presence or absence of septic shock revealed equally high sensitivity and specificity for S1P compared with the SOFA score. In a multivariate logistic regression model calculated for prediction of septic shock, S1P emerged as the strongest predictor (P < 0.001). Conclusions In patients with sepsis, serum-S1P levels are dramatically decreased and are inversely associated with disease severity. Since S1P is a potent regulator of endothelial integrity, low S1P levels may contribute to capillary leakage, impaired tissue perfusion, and organ failure in sepsis.